An Analysis of Student Decision-Making in Answering Reasoning Questions Based on Gender - Novianawati, Noor; Nahadi, Nahadi; Novia, Novia (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
The suboptimal empowerment of decision-making skills in young adolescents can hinder their ability to navigate complex choices. This research aims to determine how students make decisions when answering TIMSS science reasoning questions. This quantitative descriptive research was conducted on 178 (104 female and 74 male) 8th grade Junior High School students in Bandung. Samples came from 6 schools selected through a stratified random sampling technique. The instrument of this research is a constructed response to TIMSS questions in the cognitive domain of reasoning.  Ten questions were asked to the samples. Quantitative data analysis was used in this research to determine the tendency of students to answer questions. The results show the tendency of students to make decisions when answering questions. Both male and female students useintuition, rational, and combination intuition-rational categories.These findings highlight the multifaceted nature of student decision-making in reasoning tasks. Further research is needed to explore the factors influencing these strategies and develop effective interventions to enhance decision-making skills in this crucial developmental stage.